The effect of stress mindset on psychological pain: the chain mediating roles of cognitive reappraisal and self-identity - Shun Qiang; Jinxia Wu; Dewei Zheng; Tingting Xu; Yangkun Hou; Jianlong Wen; Jianlan Liu (Frontiers in Psychology)
BackgroundPsychological pain is the most important factor affecting suicide rates. However, the factors contributing to psychological pain in medical students remain poorly understood.ObjectiveThis study aimed to investigate the effects of a stress mindset on psychological pain and the mediating roles of cognitive reappraisal and self-identity among Chinese medical students.MethodsMedical students (N = 2056; 1,369, 66.60% female; 683, 33.40% male) from China completed multiple measures of stress mindset, self-identity, cognitive reappraisal, and psychological pain. Correlation and mediation analyses were conducted using SPSS 29.0 and Mplus 8.3.Results(1) The stress mindset was significantly negatively correlated with psychological pain among medical students. (2) Cognitive reappraisal mediated the relationship between the stress mindset and psychological pain. (3) Self-identity mediated the relationship between the stress mindset and psychological pain. (4) Cognitive reappraisal and self-identity jointly mediated the relationship between the stress mindset and psychological pain.ConclusionThe results of this study deepen the understanding of the psychological processes linking stress mindset and psychological pain and provide a valuable reference for reducing psychological pain and improving the well-being of medical students.